Benchmarking the rapid prototyping machines (RPM) for education purpose using quality function deployment (QFD) - Wan Yusoff, Wan Ahmad Yusmawiza; Badri, Zu Hazmin; Masri, Zainal; Hussin, Zahir (2009)
The important of Rapid Prototyping Machine (RPM) in the industrial sector has made the knowledge of its operation vital to the fresh graduates. The purpose of this paper is to compare and to select the best rapid prototyping machine for academic and educational purpose. All the rapid prototyping machine specification and the customer needs are compared in the approach of Quality Function Deployment. This paper analyzes the data from the user of rapid prototyping machine in various educational institutes in Malaysia which is among lecturers and students. The result offers the best machine to be used and the characteristic that fulfill the needs of the customers. The respondents own experience is the main source of information as they are directly involved in educational field and it will be support by another research about rapid prototyping machine specifications. This is a very important research as all educational fields have a standard in selecting the suitable rapid prototyping machine to give an optimum and effective learning process for students. This is a first study that applies Quality Function Deployment in benchmarking the rapid prototyping machine for the educational purpose.